2016
DOI: 10.1084/jem.20160206
|View full text |Cite
|
Sign up to set email alerts
|

pMHC affinity controls duration of CD8+ T cell–DC interactions and imprints timing of effector differentiation versus expansion

Abstract: Ozga and colleagues use intravital two-photon microscopy and quantitative whole-organ imaging to reveal the dynamics of early affinity-driven CD8+ T cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 74 publications
9
99
0
Order By: Relevance
“…In this model, pathogen-specific information may be encoded by TCR-extrinsic factors, such as ligands to other co-signalling receptors (42). This is consistent with recent in-vitro (43) and in-vivo (44) data showing that different antigen doses and affinities produce CD8 + T cells with similar response potentials. This conclusion may differ for CD4 + T cell differentiation, where antigen dose can selectively induce regulatory T cells, Th1, and Th2 phenotypes (45)(46)(47).…”
Section: Discussionsupporting
confidence: 85%
“…In this model, pathogen-specific information may be encoded by TCR-extrinsic factors, such as ligands to other co-signalling receptors (42). This is consistent with recent in-vitro (43) and in-vivo (44) data showing that different antigen doses and affinities produce CD8 + T cells with similar response potentials. This conclusion may differ for CD4 + T cell differentiation, where antigen dose can selectively induce regulatory T cells, Th1, and Th2 phenotypes (45)(46)(47).…”
Section: Discussionsupporting
confidence: 85%
“…Several animal models have demonstrated that the avidity profile of peripheral T cell populations increases following foreign antigen encounter (Busch and Pamer, 1999; Savage et al, 1999) through the selective expansion of high-affinity T cells that may better compete for limited amounts of antigen and receive a stronger signal to proliferate and survive (Bos et al, 2012; Ozga et al, 2016). In addition, regulatory T cells may preferentially inhibit low-avidity T cells (Pace et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of inflammation may therefore favor the emergence of long-lived memory CD8 + T-cells. It is also interesting to note that maturation through persistent or repeated exposure to antigen can drive the selection of specific clonotypes bearing high-affinity T-cell receptors (TCRs) (Busch and Pamer, 1999; Ozga et al, 2016; Price et al, 2005) which have been shown to suppress HIV replication more efficiently than clonotypes targeting the same antigen via low-affinity TCRs (Almeida et al, 2007; Almeida et al, 2009; Ladell et al, 2013). Increase in antigen sensitivity over time would be compatible with the progressive increase in antiviral potency that we observed for the CD8 + T-cells from controllers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the LCMV murine model of infection has shown that memory CD8 + T-cell responses expressing the transcription factor TCF1 developed during chronic infection (in an immunosuppressive environment) have a distinct molecular program, resist contraction, had increased long-term functionality, are less prone to exhaustion and are thus critical for controlling ongoing viral replication; in contrast, memory cells that are developed at the onset of infection (in a pro-inflammatory environment) become short-term effectors and are rapidly exhausted (Snell et al, 2018). Accordingly, we suggest that balanced inflammatory responses (Barouch et al, 2016) arising as a consequence of lower viral burdens in lymph nodes during acute infection in SICs might facilitate antigen-specific priming events associated with optimal memory programs (Ozga et al, 2016) and minimize the loss of CD4 + T-cells, which provide helper functions that are critical for the development of long-lived memory CD8 + T-cells (Khanolkar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%